Respiratory symptoms and some related factors in waste collection workers at 2 branches in Hanoi, 2017 - Vu Thai, Son; Tran Thi Thu, Thuy; Nguyen Thuy, Quynh (Tạp chí Khoa học Nghiên cứu Sức khỏe và Phát triển, 2021)
Objectives: Describe the current situation of respiratory symptoms in waste collection workers at 2 branches in Hanoi and some related factors, 2017 Methods: The cross-sectional study was implemented in the first 6 months of 2017. The study was performed on 796 waste collection workers at 2 branches of Hanoi Urban Environment Company Limited. The study used the American Thoracic Society and the Division of Lung Disease-1978 adult (ATS - DLD - 78a) questionnaire to collect and assess workers' respiratory symptoms. Results: Common respiratory symptoms in waste collection workers were: Cough (27.8%), phlegm (18.3%) and wheezing (15.2%). 10.8% of workers have at least one chronic respiratory symptom; 4.6% and 5.4% of workers had wheezing both day and night and wheezing to the point of difficulty breathing. The proportion of reporting respiratory symptoms in workers over 45 years old was 1.93 times that of workers younger than 45 years. Conclusions: Workers exposed to occupational hazards had a higher prevalence proportion of chronic respiratory symptoms than those who were not exposed. However, a significant association between exposure to occupational harmful factor and chronic respiratory symptoms has not been established.